2009
DOI: 10.1103/physrevlett.102.177602
|View full text |Cite
|
Sign up to set email alerts
|

Bistability of Vortex Core Dynamics in a Single Perpendicularly Magnetized Nanodisk

Abstract: Microwave spectroscopy of individual vortex-state magnetic nano-disks in a perpendicular bias magnetic field, H, is performed using a magnetic resonance force microscope (MRFM). It reveals the splitting induced by H on the gyrotropic frequency of the vortex core rotation related to the existence of the two stable polarities of the core. This splitting enables spectroscopic detection of the core polarity. The bistability extends up to a large negative (antiparallel to the core) value of the bias magnetic field … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
121
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 16 publications
12
121
0
5
Order By: Relevance
“…2 (closed circles) cannot be understood. Recently Loubens et al 15 reported an experimental result of the linear response, describing the result as an explicit expression of x 0 ðH p Þ ¼ x 0 ð0Þ½1 þ pðH p =H s Þ, where H s is the field to saturate the dot along the normal (see solid line in Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 (closed circles) cannot be understood. Recently Loubens et al 15 reported an experimental result of the linear response, describing the result as an explicit expression of x 0 ðH p Þ ¼ x 0 ð0Þ½1 þ pðH p =H s Þ, where H s is the field to saturate the dot along the normal (see solid line in Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Loubens et al 15 reported an experimental observation of the dependence of x 0 on the strength of a static magnetic field H p applied perpendicularly to the nanodot plane. However, the underlying physics have yet to be quantitatively unraveled.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a damping parameter of 0.0023 was reported for a NiMnSb film measured by resonant cavity ferromagnetic resonance. 4 The full exploitation of Heusler alloys requires an improved understanding of the intricate relationship between structural and magnetic properties, and particularly dynamic magnetic properties such as damping.…”
Section: Introductionmentioning
confidence: 99%
“…The vortex magnetization distribution stability as well as the vortex excitations were studied in Refs. [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%